The Chase: historical and ethnographic observations on 'Traditional Horse Racing' in the Eastern Cape, c. 1850 to the present - Paterson, Craig John (Rhodes University, Faculty of Humanities, Department of History, 2019)
This thesis examines the development of a horse racing sport, umdyarho wamahashe, as it is practised in the former-bantustans of the Eastern Cape Province. Using varied source material "“ ethnographic, archival and oral "“ it provides a guide to understanding the historical development of umdyarho events and their meaning to participants. By drawing together available 'fragments' of material on horses and horse racing in the former-bantustans of Transkei and Ciskei, it argues that horse racing is derived from a pre-colonial cattle racing tradition which was made impossible by a collision of environmental pressures and colonial responses to them. It goes on to show how horses came to take on a 'symbol set' of masculine power and "growing up." The nexus of horses, rapidly assimilated into daily life, and the changing material conditions confronting the people of the Eastern Cape, made horse racing an ideal outlet through which men might regain a sense of power in conditions which eroded their sense of control over their daily lives, and, as a result, their perceived masculinity. This thesis argues that through horse races, people of the Eastern Cape were provided an space in which they could at once celebrate their legacy (by acting as their 'forebears' did) and their potential (by showing who they would like to be, through the deployment of the horse as a symbol). It concludes by discussing and how the imposition of change from outside threatens the 'spirit' of this sport.
Keywords: Horse racing -- South Africa -- Homelands; Masculinity -- South Africa - Homelands -- History; Migrant labor -- South Africa; Masculinity in sports -- South Africa -- Homelands Group identity -- South Africa - Homelands -- History; South Africa -- Social conditions -- 1961-1994; South Africa -- Politics and government -- 20th century